Modelagem de Tráfego em Redes PLC (Powerline Communications) Utilizando Cadeias de Markov - SANTOS, Christiane Borges (2009)
This work is motivated by a growing interest in the power lines' applicability as an alternative means of propagation for communication signals, and presents an analysis of VoIP's (Voice over IP) traffic and data transfer using BPL / PLC (PowerLine Broadband / PowerLine Communication) network. We describe the main characteristics of the BPL / PLC and HomePlug standard. As the physical transmission technology used by the BPL / PLC for data transfer is hostile, and it was not developed for this purpose, traffic modeling can be useful for planning and design these networks. A model is proposed based on MMFM (Markov Modulated Fluid Models) to characterize the traffic data and VoIP into PLC networks. Simulations and comparisons were made with other models such as Poisson and MMPP (Markov Modulated Poisson Process). The results were obtained by experiments in low-voltage PLC networks (indoor environment), using a 4,3MHz to 20,9MHz bandwidth